ANALISIS YURIDIS PEMBERIAN KREDIT OLEH KOPERASI TERHADAP PENGUSAHA KECIL DAN MENENGAH BERDASARKAN UU NO.17 TAHUN 2012 TENTANG PERKOPERASIAN (Studi Pada Koperasi Kredit Union Sejahtera Tebing Tinggi) - Gunawan Sibarani; Tan Kamello; Mahmul Siregar; Keizerina Devi (Universitas Sumatera Utara, 2014)
ABSTRACT Cooperatives as people’s economic movement give their contribution to small and middle businesses in increasing the welfare, especially for their members. A cooperative is both the guidance for people’s economic policy and a part of national economic order. How is the regulation of giving credit to small and middle businesses according to Law No. 17/2012 on Cooperatives? How is the implementation of giving credit to small and middle businesses at Koperasi Kredit CU Sejahtera, Tebing Tinggi? Are there any obstacles and how to solve them? The regulation of giving credit in Law No. 17/2012 on Cooperatives should be in savings and loan. In this case, the credit at Koperasi Kredit CU Sejahtera, Tebing Tinggi is given only to its registered members. The main obstacle is the incapability of its members to pay off the credit. It is recommended that the cooperative adapt its statutes to Law No. 17/2012 on Cooperatives by amending USP to KSP, giving credit should be based on the capability and compatibility, and special advisors who give sanction to fraudulent field workers should be supported. Kata Kunci : Savings and Loan Cooperative, Small and Middle Businesses, Kopdit CU Sejahtera Tebing Tinggi